28.3k views
3 votes
Find 3+root 2/3-root 2=a+b root2

User MustafaP
by
6.0k points

2 Answers

2 votes

Answer:


(11)/(7) +
(6)/(7)
√(2)

Explanation:

Given


(3+√(2) )/(3-√(2) )

Multiply the numerator/ denominator by the conjugate of the denominator.

The conjugate of 3 -
√(2) is 3 +
√(2) , thus

=
((3+√(2))(3+√(2)) )/((3-√(2))(3+√(2)) ) ← expand numerator/ denominator using FOIL

=
(9+6√(2)+2 )/(9-2)

=
(11+6√(2) )/(7)

=
(11)/(7) +
(6)/(7)
√(2) ← in the form a + b
√(2)

with a =
(11)/(7) and b =
(6)/(7)

User Bryan Ray
by
4.8k points
4 votes

Answer:

a =
(11)/(7) ; b =
(6)/(7)

Explanation:


(3 + √(2))/(3 - √(2) ) = a + b√(2) \\\\

Rationalising
(3 + √(2))/(3 - √(2) ) gives :-


(3 + √(2))/(3 - √(2) ) = ((3 + √(2))(3 + √(2)))/((3 - √(2))(3 + √(2)) ) = ((3 + √(2))^2)/(3^2 - (√(2))^2 ) = (11 +6√(2) )/(7)

Comparing
(11 + 6√(2) )/(7) with
a + b√(2) gives

a =
(11)/(7) & b =
(6)/(7)

User Jacob Honeyhume
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.